Relapse of ulcerative proctocolitis during treatment with non-steroidal anti-inflammatory drugs. Issue 667 (May 1981) - Rampton, D. S.; Sladen, G. E.
Abstract : In four patients with inactive ulcerative proctocolitis, oral administration of non-steroidal anti-inflammatory drugs appeared to precipitate relapse. These observations suggest that inhibitors of prostaglandin synthesis should be used with care in patients with this disease, and are consistent with the hypothesis that prostaglandins may have a protective role in the lower as well as the upper gastrointestinal tract.